Persepsi Petani terhadap Kompetensi Penyuluh Pertanian di Kecamatan Payakumbuh, Kabupaten Lima Puluh Kota - Mega Amelia Putri; Veronice Veronice; Gusdea Ananda (Jurnal Penyuluhan, 2022)
Agricultural extension is a lesson for the main actors and business actors so that they can help themselves in obtaining information related to the sustainability of their farming business. This study aims to: 1) analyze farmers perceptions of the competence of agricultural instructors, 2) analyze the relationship between farmer characteristics and extension activities with the level of farmers perceptions of agricultural instructor competencies based on the Regulation of the Minister of Agriculture No: 55/Permentan/KP. 120/7/2007. This study used a survey method with a total of 39 respondents. The results of descriptive and inferential analysis found that farmers had low perceptions of the competency level of agricultural extension workers. Extension workers are considered not optimal in carrying out their roles according to their duties and responsibilities. The factors that significantly influence the level of farmers perceptions of the competence of agricultural extension workers are the involvement, intensity and interaction of farmers in extension activities. This shows that the more frequent the involvement, the intensity of the meetings and the interaction of farmers with agricultural extension workers, the level of farmers perceptions of the main extension activities, extension planning, extension programs, application of extension methods, farmer self-help development, regional development, as well as the development of cooperative relationships with government agencies and non-government is higher.